CHARACTER EDUCATION IN PRIMARY SCHOOLS(LITERATURE REVIEW STUDY) - Takiling, Wahid (Teaching English as a Foreign Language Overseas Journal, 2023)
Character education is an effort to form good attitudes, behavior and actions in individuals so that they can create people with character. The character education curriculum has become mandatory at all levels of education in Indonesia, including basic education. These character learning efforts are carried out in an integrated manner and are carried out through familiarization with teaching and learning activities and other activities. An understanding of character education in elementary schools is seen as having good character in forming students' morals which ultimately supports the creation of a better society. This article aims to deepen the concept of character education, the learning methods used, and the impact of character education on elementary school students